Spaces and spatial qualities of traditional urban marketplace: a case study of Pasar Payang - Mohd, Siti Zulaikha; Zakariya, Khalilah; Kamaruddin, Zumahiran (2014)
The rich qualities of the traditional marketplace are attributed to its components, such as the products, people and spaces. There is a significant need to examine the characteristics of the marketplace and how they contribute to the setting of the market, as these shape people’s experiences. This is important to ensure that the development of traditional urban marketplace can continue to flourish in the future, alongside their cultural and heritage values. This paper aims to illustrate the characteristics of a traditional urban marketplace through its spaces and spatial qualities, based on a case study of Pasar Payang, a market located in the city of Kuala Terengganu, Malaysia. The study was conducted through site inventory, observation and photographic documentation on the spaces and setting inside the marketplace. The findings reveal that there are different categories of spaces that make up the marketplace. Vendors adapt and alter their spaces in diverse ways, and this influences the spatial qualities of the market. This study concludes that spaces and activities at the market compose the spatial qualities of the marketplace, which make the market unique in its own way. Therefore, it is essential that designers and planners take into account these aspects in the development of the traditional urban marketplace in the future to ensure that the market can sustain its culture.